2013
DOI: 10.1186/1749-8090-8-16
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of temporary vascular occluder poloxamer 407 Gel on the endothelium

Abstract: BackgroundCoronary occlusion techniques during OPCAB may lead to an endothelial damage to the target vessel. The adverse effects of these techniques are well-known, and researches have been trying to find out new materials to occlude the coronary artery without an endothelial damage. In the present study, we investigate to the endothelial damage in the rat aorta which is occluded by Poloxamer 407 gel.MethodsForty-five rats were randomized in three groups: (1) segment of the aorta was occluded with Poloxamer 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…38,39 Some poloxamer-based devices are also clinically utilised in the U.S. and in Europe, for instance the Pluronic® 407 gel (LeGoo® from Pluromed Inc.) used as off-pump coronary bypass (rapid gel injection aer arteriotomy of the abdominal aorta in order to occlude the vessel -Poloxamer 407becomes solid within a few seconds). 40 A number of clinical trials now involve Pluronic® polymer containing formulations (Table 1).…”
Section: Pluronics® As Surfactants and Gelation And Coating Agents Fo...mentioning
confidence: 99%
“…38,39 Some poloxamer-based devices are also clinically utilised in the U.S. and in Europe, for instance the Pluronic® 407 gel (LeGoo® from Pluromed Inc.) used as off-pump coronary bypass (rapid gel injection aer arteriotomy of the abdominal aorta in order to occlude the vessel -Poloxamer 407becomes solid within a few seconds). 40 A number of clinical trials now involve Pluronic® polymer containing formulations (Table 1).…”
Section: Pluronics® As Surfactants and Gelation And Coating Agents Fo...mentioning
confidence: 99%
“…It is likely that additional undocumented endothelial denudation injuries are created with high incidence during the process of stent placement. In fact, studies in animal models have indicated that surgical clamping alone is sufficient to cause loss of the endothelial layer [15,16]. Catheter contact with the vessel wall is also sufficient to cause denudation, an underappreciated source of endothelial injury [17].…”
Section: Consequences Of Arterial Denudation: Thrombosis and Restementioning
confidence: 99%
“…Arterial denudation injury due to percutaneous interventions, such as balloon angioplasty and vascular stenting, result in early and late vascular thrombosis and restenosis and contributes to recurrent ischemic events 3,12 . Interestingly, surgical vascular clamping has also been implicated as a cause of arterial denudation, expanding the scope of the problem to patients undergoing any vascular procedure, whether percutaneous or open 13 . While impaired re-endothelialization is a fairly recognized cause of thrombosis and restenosis, the molecular mechanisms surrounding re-endothelialization have been difficult to elucidate.…”
Section: Discussionmentioning
confidence: 99%